Parenting Styles, Depressive Symptoms, and Problematic Online Game Use in Adolescents: A Developmental Cascades Model - Gan, Xiong; Li, Hao; Li, Mengmeng; Yu, Chengfu; Jin, Xin; Zhu, Congshu; Liu, Yifan (Frontiers in Public Health, 2021)
Abundant empirical research demonstrates a relationship between parenting style and adolescent Internet gaming disorder (IGD), but the direction and underlying mechanism of this association remain unclear. Using a one-year longitudinal design across three time points, the present study explored interrelations among parenting styles, depression and IGD from the theoretical perspective of the developmental cascade model and examined whether depression mediates the relationship between parenting style and IGD. A sample of 1041 children (46.3%boys) was recruited from two junior middle schools in China. Results confirmed the cascade effects and showed that the reciprocal effect of parenting style, depression, and IGD was significant, and parental control and IGD can predict each other via depression. Knowledge regarding the direct and underlying mechanisms between parenting style, depression, and IGD provides reference suggestions for the prevention and intervention of adolescent depression and internet gaming disorder.